V.V. Maslovskiy — The Father Of Medical Dynasty - L.D. Sidorova (Саратовский научно-медицинский журнал, 2009)
Biographic data about professor V.V. Maslovskiy that reflect his scientific and practical contribution to the development of nativ morphology have been presented in the article